Pengaruh Trust, Perceived Value, Brand Image Dan Satisfaction Terhadap Repurchase Intention Batik Air Di Jakarta Dan Tangerang - Adeline Felicia Lianto (Universitas Tarumanagara, 2019)
The aim of this research is to find out whether trust, perceived value, brand image and satisfaction give impacts on repurchase intention in flight industry. The samples are collected by using convenience method by giving out questionnaires to 122 customers of a flight company in Jakarta and Tangerang who have experience of using this flight for at least 2 times in last 5 years.The technique of data analysis used in this research is multiple regression analysis.The results showed that: (a) there is a significant and positive effects between trust and repurchase intention; (b) perceived value do not create significant impact towards repurchase intention; (c) brand image gives significant and positive effect to repurchase intention; (d) there is a significant and positive effects between satisfaction and repurchase intention.